Aminoacyl-tRNA synthetases activity as a growth index in zooplankton - Yebra, Lidia; Hernández-León, Santiago (Journal of Plankton Research, 2004)
A simple method for the assay of aminoacyl-tRNA synthetases (AARS) activity was modified for application in planktonic crustaceans as an index of somatic growth. The cladoceran Daphnia magna was cultured in the laboratory and its AARS activity measured without substrate addition. The relationship between the enzyme activities of animals of similar age and individual biomass growing at different rates was tested. A significant relationship was found between AARS activity and somatic growth in terms of both protein and dry weight. 356 351 1,189 Q2 SCIE